geometry

Find the value of x.
x = 18x = 22.5x = 30x = 54
is like a like two line almost forming an X and on the left side it says (x+90) and on the right side it says 4x

  1. 0
  2. 4
asked by joey
  1. I recommend you get a tutor, or a study buddy. You do no know how to read math symbols, and as a result are making us guess what you are reading.

    1. 0
    posted by bobpursley

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra

    2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3 how will solve it? well you first multiply it out: 6x-14+12x+8=30x+54+3 you combine like terms 18x-6=30x+57 -12x=63 x=-63/12
  2. math, algebra

    can someone correct this for me or help me. 6x^2y^3+ 9x^2y^3 divided by 3x^2y^2 my solving and answer is: 15 x x y y y ---------- = 5y 3 x x y y Looks good to me. I've never thought of showing x^2y^3 as xxyyy. That a neat wrinkle.
  3. Algebra: factoring

    I need to find the value of x. 9x^3 + 9x = 30x^2 It's confusing because apparently I have to do 9x^3 + 9x and then add the + 30x^2 to it, and then make it equal 0, so it ends up like this: 9x^3 + 9x + 30x^2 = 0 And afterward, I
  4. algebra

    factor out the greatest common factor from the expression 18x^5+48x^2-30x
  5. factoring

    Question: 30x^3 + 18x^2 - 5x - 3 My Answer: 6x^2(5x+3)(-5x-3) Is that right. If not can you please correct my answer and tell me what to do! Thanks :)
  6. math (binomial exp)

    the Q is : Given that (1+ax)^n = 1 + 30x +375x^2+.... find the values of the constants a and n . I know that : (i am writing (n 1) as the coefficient of n) (n 1) *ax = 30x (n 2) *(ax)^2 = 375x^2 which can be written as (n 1)* a =
  7. Math

    Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+18x-36
  8. Math

    9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and the vertices of this ellipse. 9x^2+16y^2-18x+64y-71=0 9x^2-18x+16y^2+64y=71 9(x^2-2x)+16(y^2+4y)=71 9(x^2-2x+1)+16(y^2+4y+4)=71
  9. Algebra

    checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
  10. Algebra

    Convert the simplified parabolic equation y=3x^2-30x-7 to standard form. 3x^2-30x-7 3x^2 -30 x -7 +75 -75 3(x^2 -10x + 25) -82 3(x-5)^2 -82 or y = 3(x-5)^2 -82 check that.

More Similar Questions